Legacy Prof. James H. Liu Untuk Psikologi Sosial Indonesia: Sebuah Obituari - Hakim, Moh. Abdul (Jurnal Psikologi Sosial, 2025)
Our collaboration began when James, Mark Woodward (Anthropologist – Arizona State University), and Nora Fisher Onar (Political Scientist – University of San Francisco) invited me – then still a master's student in Psychology – to assist in their cross-cultural, multidisciplinary research. At that time, they were studying critical junctures - how an event in the corridor of history shapes the direction of a nation or society (Liu, Onar, & Woodward, 2014). It was a profound experience for me personally. Not only because of its thought-provoking theme, but also because it was here that I first directly observed and learned how psychology, which mainly concerns micro phenomena (human thoughts and behaviors), can speak about complex and broad (macro) issues such as nation buildings. Later, I realized that this was James's strength and unique character as a scholar; he was able to marry psychological theories and methods with various fields of study and build collaborations with many scientists from diverse academic backgrounds and countries/cultures. From this research collaboration, and with James's encouragement and supervision, I learned to write academic article and published it in an international journal (Hakim, et al., 2015).